The Effect of the First Issue of Oplosan on the Kompas.com Online News Portal on the Level of Trust of Tiktok Followers @kompascom towards Pertamina - Deni Budiarto; Edy Sudaryanto; Hajidah Fildzahun Nadhilah Kusnadi (Journal of Communication, Sustainability, and Empowerment, 2026)
The issue of adulterated Pertamax fuel arose at the end of February 2025 due to allegations of corruption and fuel adulteration by PT Pertamina Patra Niaga, which caused material and non-material losses and led to a crisis of public confidence in Pertamina. This issue spread widely through various media outlets, including Kompas.com and the TikTok account @kompascom, which has more than 6 million followers. The purpose of this study was to determine the effect of exposure to the Pertamax adulteration issue on the Kompas.com online news portal on the level of trust of followers of the @kompascom TikTok account in Pertamina. This study used an explanatory quantitative research method with behaviorism and stimulus-response (S-R) theory. Sampling was conducted using purposive sampling and the sample was determined using the Slovin formula. The research population consisted of followers of the TikTok account @kompascom who use Pertamax and have accessed news related to this issue. The results of the study show that exposure to the issue of Pertamax adulteration (X) has a significant negative effect of 0.823 on the level of trust (Y), which means that the higher the exposure to the issue, the lower the level of trust. The exposure to the issue, the lower the level of trust.